Akute Brustschmerzen in der Hausarztpraxis – Unsicherheit zwischen abwartendem Offenhalten und Notarzteinsatz - Schmiemann, Guido; Frantz, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2019)
Acute chest pain is a frequent reason for encounter in primary care. In contrast to hospital/emergency departments serious diseases like acute coronary syndrome or a pulmonary embolism are relative rare in primary care. This overview presents the diagnostic work up and decisions for transfer to the hospital setting in patients with acute chest pain.
Keywords: Brustschmerzen; hausärztliche Versorgung; Herzinfarkt; Lungenembolie